Power and Mass-Media: Adjusting of Effective Co-Operation - Mytko, Antonina (The Copernicus Journal of Political Studies, 2018)
The article is about practical recommendations of improvement of mutual relations are offered between ЗМК and public power which will assist forming of positive image of power. It is worked out to recommendation to the informative institutes in relation to realization of informative campaigns, planning PR, expansion of the system of instruments for more effective co-operation. The purpose and objectives of the research is to consider the relationship between a transmitter and public authorities offer practical recommendations to improve the relationship between media power to facilitate a positive image of tchem government. Methods: systematic and functional retrospective futurological, analysis and synthesis. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14762